Political attitudes in adolescence and emerging adulthood: Developmental changes in mean level, polarization, rank‐order stability, and correlates. (11th April 2015) - Rekker, Roderik; Keijsers, Loes; Branje, Susan; Meeus, Wim
ABSTRACT: This three‐wave cohort‐sequential longitudinal study ( N = 1302) examined the development of two core political attitudes, economic egalitarianism and ethnocentrism, among Dutch youths between age 12 and 31. Longitudinal regression analyses revealed a curvilinear mean level development for both attitudes, reflecting an increased disagreement with economic redistribution and multiculturalism around late adolescence. Furthermore, attitudes became decreasingly polarized (i.e., less extreme) and increasingly stable with age. Finally, several effects of attitudes' correlates gradually changed: The effect of educational level on ethnocentrism increased with age, whereas the effect of gender diminished. Regional effects on ethnocentrism developed as youths resided in a new area. No age‐related change was found in the effect of parental SES. Overall, these findings support the idea that attitudes mature during the formative phase of adolescence and that this process slows down during emerging adulthood. Furthermore, these results support developmental explanations for the association between attitudes and their correlates.